A different approach for soliton solution of the improved Boussinesq equation - İnç, Mustafa; Evans, DJ (Taylor & Francis Ltd, 2004)
In this article, we solve the improved Boussinesq equation (IBE) by Adomian's decomposition method. By using this method, the solutions are calculated in the form of a convergent power series with easily computable components. Soliton solutions of this equation are used to examine the accuracy and efficiency of the proposed method. We prove in this article the convergence of the Adomian method applied to the IBE. The numerical results show that only few terms are sufficient to obtain accurate solutions.
Keywords: Adomian decomposition method; Adomian polynomials; the improved Boussinesq equation